Characterization of GmMATE13 in its contribution of citrate efflux and aluminum resistance in soybeans - Wang, Zhengbiao; Liu, Yuanqi; Cui, Wenmo; Gong, Li; He, Ying; Zhang, Qingxiu; Meng, Xiangxiang; Yang, Zhenming; You, Jiangfeng (Frontiers in Plant Science, 2022)
Citrate exudation mediated by a citrate transporter of the MATE protein family is critical for resisting aluminum (Al) toxicity in soybeans. However, the expression patterns of citrate transporter genes differ under Al stress. Thus, exploring the responsive pattern of GmMATEs in response to Al stress is of great importance to understand the Al resistance mechanism in soybeans. In the present study, the phylogenetic analysis, transcriptionally expressed pattern, and function of GmMATE13 were investigated. The results show that soybean GmMATE13 is highly homologous to known citrate transporter proteins from other plants. Under Al exposure, the transcript abundance of GmMATE13 was increased during a 24 h Al treatment period. The expression of GmMATE13 is specifically induced by Al exposure, but not by the status of Fe, Cu, Cd, or La. Moreover, it was also highly increased when soybean seedlings were grown on acidic soil with a high Al content. Subcellular localization showed that GmMATE13 was localized on the plasma membrane when it was transiently expressed in Arabidopsis protoplasts. Investigation of tissue localization of GmMATE13 expression by investigating GUS activity staining under control of the GmMATE13 promoter showed that it was mainly expressed in the central cylinder in the root tips of the soybean under Al-free conditions, yet extended to cortical and epidermis cells under Al stress. Finally, overexpressing GmMATE13 in soybean hairy roots enhanced Al resistance by increasing citrate efflux. Collectively, we conclude that GmMATE13 is a promising candidate to improve the resistance of soybean to Al toxicity in acidic soil.